Analysing visual and textual content of tourism brochures: a case of Malaysian destination image - Ramachandran, Sridar (Tourism Educators Association of Malaysia, 2005)
The purpose of the study is to reveal the meaning of destination images that is projected in tourism brochures. Semiotic analysis approach is used to achieve this objective. This paper adapts the 4-phase research process of design principle, data elicitation, data analysis and knowledge interest. The work of Saussurre, Peirce and Barthes is reviewed in understanding the structure of meaning from both visual and textual angles prior to applying the semiotic analysis approach within the destination image context. The findings of this paper discuss the underlying structure of meaning of Malaysian destination images from a British perspective.